Analisis Kemampuan Penalaran Proporsional Siswa dalam Menyelesaikan Soal Matematika pada Materi Lingkaran - Awi Dassa; Muhammad Dinar; Hervina Dewi Astuti (Issues in Mathematics Education (IMED), 2022)
This research aim to analyze student ability of student's proportional reasoning in solving mathematics on circle topic. Two students from grade IX were selected as in term results of math pre-requisite ability test. then, proportional reasoning test was given to subject and interview related to it. The results show that (1) all subjects complete indicator in additive thinking ability, (2) all subjects complete multiplicative thinking ability, (3) second subject only which complete indicator in ability to use a reasonable or appropriate ratio while first subject not complete this indicator, (4) all subject not complete indicator in ability to build a unit structure (grouping), (5) all subject not complete indicator in ability to understand invariance